Warfarin Care: Warfarin Management System for Older Adults - Hnoohom, Narit; Wongpatikaseree, Konlakorn; Poungkaew, Autchariya; Kongwatcharapong, Junporn (Journal of Applied Informatics and Technology, 2025)
Warfarin Care emerges as a transformative solution in digital healthcare for the elderly reliant on warfarin. Addressing specific needs, Warfarin Care serves as a communication and information exchange among medical personnel, elderly patients, and family members or caregivers. With a user-friendly interface, rigorous content evaluation, and a shared database architecture, Warfarin Care endeavors to mitigate medication errors and augment overall treatment outcomes. Through the integration of risk assessment, medication history, and warfarin knowledge, medication reminders, and educational tools, the application fosters a deeper understanding of proper medication behavior. The research is based on the clinical trial, in which 60 cases of elderly patients and family members, 30 elderly patients, and 30 family members or caregivers were selected as the sample receiving treatment in the outpatient department of Sakonnakhon Hospital. The study from the clinical trial revealed that the majority of elderly participants fall within the 60–69 age group, predominantly women and married. The data reveals high satisfaction among both elderly users and caregivers, underscoring Warfarin Care’s positive impact on enhancing knowledge, confidence, and support for proper medication adherence with user-friendly communication. Users agreed that the use and suitability of the Warfarin Care application had an average of 4.57 and a S.D. of 0.57 from elderly users and an average of 4.67 and a S.D. of 0.61 from caregivers or family members. The robust data analysis utilizing mean and standard deviation values underscores the application’s effectiveness.